Legacies of the South Korean Mass Housing - Brossa, Marc (ZARCH, 2015)
The mass housing policies of the South Korean developmental state during the second half of the 20th century managed to overturn the traditional preference for single-storey housing in less than one generation. The exponential growth of the GDP since 1961 occurred hand in hand with the consolidation of apartment complexes as the default element of city-making and as the default domestic setting. As a result, they today are the residential choice of more than 50% of the population of Seoul. Not only have housing estates addressed the chronic housing shortage present in the capital since the 1920s, but they have also been a key element in the fast urbanization of the country and in the formation of a new urban middle class. Nowadays, there are evidences that the socio-economic model which supported the emer- gence and generalization of mass housing estates in Seoul has changed, questioning the very durability of the model. The objectives of the article are twofold. Initially, it describes the particularities of the Korean mass housing policy, the reasons for its success despite being perceived as a failure in the West, and its shared characteristics with other East Asian developmental regimes. Secondly, it discusses its legacy, both in terms of the know-how that Korean construction companies are trying to export to developing countries, but also in terms of the consequences which the maintenance of this large built urban stock will hold in the near future.